Assessing nominal GDP targeting in the South African context - Kenneth Creamer; Robert Tregathen Botha (Central Bank Review (CBR), 2017)
The main purpose of this research paper is to determine whether Nominal GDP targeting as a monetary policy regime would be superior to Inflation targeting in minimising the South African Reserve Bank's loss function. This is done by algebraically deriving the necessary conditions for Nominal GDP targeting to dominate Inflation targeting using two different forms of loss functions. The first form includes price stability and output stability, while the second form includes both price and output stability and adds currency fluctuation into the loss function, both using data from 1993Q1 to 2014Q1 and uniquely incorporating data from the mining sector due to the sector's key role in the South African economy. Based on these results and practical issues of Nominal GDP targeting, such as the possibility of enhancing the severity of stagflation, this paper does not recommend Nominal GDP targeting as a monetary policy framework for South Africa.
Keywords: 330; Monetary policy; Nominal GDP targeting; Income targeting; Inflation targeting; SARB; Central bank loss function